2000
DOI: 10.1071/ch00016
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Some Spiro Oxindole Alkaloids Through Cycloaddition Reactions of 3-Methylideneindolin-2-one

Abstract: 3-Methylideneindolin-2-one (3-methylideneoxindole) (1) was prepared in 60–89% yield by flash vacuum pyrolysis of the acetate or methyl carbonate of 3-hydroxy-3-methylindolin-2-one, and was fully characterized, but application of the same procedure to 3-hydroxy-5-methoxyindolin-2-one did not give useful yields. Cycloaddition reactions of CH2= +NR–CH2 – and of the related ylide (25) (from 1-(trimethylsilylmethyl)piperidine-2-carbonitrile and AgF) to 3-methylideneindolin-2-one (1) gave 4–20% yields of spiro oxind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Scheme summarizes the synthesis of the required building block 2 . Subjecting 5‐methoxyisatin ( 5 )6 and methoxy enone 6 to a two‐step Friedlander quinoline synthesis7 via intermediate 7 afforded the keto carboxylate 8 , which was reduced in situ (NaBH 4 ) to furnish the tricyclic lactone 9 in 86 % overall yield. Exchange of the phenolic methyl group for a DMB group led to 10 (50 % overall yield for the two steps).…”
Section: Methodsmentioning
confidence: 99%
“…Scheme summarizes the synthesis of the required building block 2 . Subjecting 5‐methoxyisatin ( 5 )6 and methoxy enone 6 to a two‐step Friedlander quinoline synthesis7 via intermediate 7 afforded the keto carboxylate 8 , which was reduced in situ (NaBH 4 ) to furnish the tricyclic lactone 9 in 86 % overall yield. Exchange of the phenolic methyl group for a DMB group led to 10 (50 % overall yield for the two steps).…”
Section: Methodsmentioning
confidence: 99%
“…To conclude, we have aimed to synthesize different 1-(phenylsulfonyl)indolines (scaffold 32 ), being substituted in the 1′-pyrrolidine nitrogen with either basic-nitrogen containing, or lipophilic groups, presented in Scheme 4 —compounds 39a – b . Based on these considerations, first we benzylated [ 44 ] the tryptoline ( 25 ) to afford 36a , further converting it to the corresponding spiro-derivative [ 45 ] 37a . The reduction of the oxindole oxo-group was performed by applying borane-tetrahydrofuran complex in refluxing absolutized tetrahydrofuran [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Horvath and co-workers reported that azomethine ylides generated from silylaminonitriles and 3-methyleneindolin-2-one react to give the corresponding cycloadduct in 70% yield . However, the dipolarophile was generated by flash vacuum pyrolysis and did not seem compatible with the synthesis of the methoxy-substituted derivative we required.…”
mentioning
confidence: 95%